(untitled) (Interdisciplinary Studies Journal, 2024)
Human Rights Education (HRE) is based on the concept of being an educational process focused on aspects of a humanizing and professionalizing education. It is conditioned to a dimension of education that encompasses principles of respect for the dignity of the human person, in a reformulation that is guided by the training of teaching citizens and educational practices. The legal aspects that constitute public policies for teacher training in the context of Human Rights are supported by various regulations, such as Resolution no. 02/2015 of July 1, 2015, within the regulatory scope of the Full Council of the National Education Council, with standards for training practices that meet education regarding Human Rights. The objectives of this study are aimed at understanding teacher training processes and their relationship with human rights practiced in the context of education. The methodology used was literature review. The results show the relevance of attending to a teacher training dynamic for a social context regarding Human Rights and which requires a constant and updated model of support for the teacher so that their students can exercise the context of respect in a society that values the figure human.